Tool, toy and tutor: Subjective experiences of digital self-tracking. (March 2018) - Lyall, Ben; Robards, Brady
Since the advent of the smartphone, users have become accustomed to alerts, notifications and reminders to interact with their internet-connected devices. But how do people make sense of prompts to exercise, eat or sleep? Digital self-tracking is a phenomenon that has grown substantially in recent years. However, despite some notable exceptions, there is still little sociological research into how users of wearable devices and apps subjectively experience self-tracking. This article draws on findings from a small qualitative study with 11 participants to reveal eminent themes in how users make sense of their self-tracking. Utilising and extending Lupton's theorising of self-tracking, we argue for triple roles of self-tracking devices; 'tool', 'toy' and 'tutor'. This trichotomy helps to characterise the use of self-tracking devices and apps, allowing us to reflect on the wider, ongoing implications of self-tracking.